2014
DOI: 10.1007/s10841-014-9722-9
|View full text |Cite
|
Sign up to set email alerts
|

Ant community structure and response to disturbances on coastal dunes of Gulf of Mexico

Abstract: Coastal dunes are complex and fragile ecosystems. The decrease in environmental stressors from sea to inland creates zonation patterns of habitats, which support high biodiversity. Although coastal dunes have been examined in primary succession studies for more than 100 years, invertebrates have received much less attention than other taxa. In this study, we examined ant community composition and its relationship with vegetation structure on dunes, and used ants as indicators to reveal the influence of anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 110 publications
2
9
0
Order By: Relevance
“…Overall, the urban sites covered by pavement and building and hosted less ant species than suburban and rural sites. This result is similar to studies which found that ant diversity along urbanization gradients is lowest near urban sites (Yamaguchi 2004;Lessard and Buddle 2005;Buczkowski and Richmond 2012;Chen et al 2015) and is in contrast with others studies which found that ant richness does not decline (Gibb and Hochuli 2003), but rather increases with urbanization (Uno et al 2010). There are two main factors that influence ants' species richness and composition in urban areas: urbanization and invasion by tramp species.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, the urban sites covered by pavement and building and hosted less ant species than suburban and rural sites. This result is similar to studies which found that ant diversity along urbanization gradients is lowest near urban sites (Yamaguchi 2004;Lessard and Buddle 2005;Buczkowski and Richmond 2012;Chen et al 2015) and is in contrast with others studies which found that ant richness does not decline (Gibb and Hochuli 2003), but rather increases with urbanization (Uno et al 2010). There are two main factors that influence ants' species richness and composition in urban areas: urbanization and invasion by tramp species.…”
Section: Discussionsupporting
confidence: 89%
“…Termites showed significant increases in diversity in forested ecosystems while decreased in managed agricultural lands of Benin (Hausberger & Korb, 2016). In dunes, although not significant, ant also decreased in number as bushes recover coastal dunes in United States (US), but their diversity increased showing unique ant assemblages in the (less degraded) bushes area (Chen et al, 2014).…”
Section: Species Identificationmentioning
confidence: 97%
“…This group occurs in several modern environments, including grasslands and vegetated zones close to or inside tropical forests, and is restricted to the latitudinal interval 0º to 50º in the Northern and Southern hemispheres (Lee and Wood, 1971;Su, 2003). Unlike ants that commonly nest in coastal dunes (e.g., Chen et al, 2015), termites are seldom registered in these settings. A few studies reported termite nests in sandy soils in coastal environments (e.g., Kaiser, 1953;Araújo and Fontes, 1979;Fontes, 1979Fontes, , 1982Fontes, , 1992Vasconcellos et al, 2005;Diehl et al, 2014Diehl et al, , 2015Santos, 2015), mostly in denser vegetated areas of restinga ecosystems (e.g., Moura and Machado, 2017).…”
Section: Introductionmentioning
confidence: 99%